Revision of the genus Procoryphaeus Mazur, 1984 (Coleoptera: Histeridae: Histerinae: Exosternini) - Lackner, Tomáš (Zootaxa, 2015)
The genus Procoryphaeus Mazur, 1984 is revised herein. It contains three species: Procoryphaeus violaceus (Lewis, 1905) from Thailand: Tenasserim Mountains; Malaysia: Borneo: Sabah; Indonesia: Java, Sumatra and Papua, Procoryphaeus pilosus (Lewis, 1893) from Tanimbar Island, Indonesia and Procoryphaeus wallacei (Marseul, 1864) from Indonesia: Papua. All type specimens are figured, and male genitalia of P. violaceus are drawn. Lectotypes of Pachycraerus (Coryphaeus) wallacei Marseul, 1864, Coryphaeus violaceus Lewis, 1905 and Coryphaeus pilosus Lewis, 1893 are designated. The exact identities of P. violaceus and P. wallacei species remain unclear since they are morphologically very similar and both respective type specimens are females. A key to species is given.